IDIOMATIC TRANSLATION METHOD OF ENGLISH INDONESIAN TRANSLATION (A content analysis of a book “the Twilight Saga Breaking dawn” by Stephenie Meyer) - Ferawaty Puspitorini; Haris Hamdani (STKIP PGRI Tulungagung, 2024)
The purpose of the research was to analyze the idiomatic translation found in “The Twilight Saga Breaking Dawn” By Stephanie Meyer. The result of the research is the idiomatic translations method which is found in the novel and analyzed by using the theory of translation from Newmark. Based on the data analysis, the writer found some proofs that the data which were translated used idiomatic translation method. In analyzing translation process, the writer compared with other translation methods. The purpose was that the writer showed the translation method used by the translator was idiomatic translation method. In translation, the translator paid attention to the meaning of source language so that the message in target language can be received by the readers.